"Eu grito pelo povo!"– transgressão e condição feminina em Orlanda Amarílis e Rachel de Queiroz: Um diálogo com o mito de Medeia - Paula, Daniele LIma de (2024)
The present research aims to investigate in the novel "As três Marias" (1939) by the writer Rachel de Queiroz and in the short story "A casa dos mastros" (1989) by Orlanda Amarílis how the conduct of the characters Maria Augusta and Violete engages with the myth of Medea, based on the version of Euripides (431 B.C). Supported by Reception Studies, this research reflects on the role of women in Antiquity and how it can still be relevant, reconfiguring itself in 20th-century narratives, especially since these are women writers who are part of a context marked by the roots of the colonizer's culture, a situation that takes up the patriarchal model, with women in a subordinate position. Therefore, we chose to focus on building the object of our investigation on the transgressive nature of Medea, recognized in the characters Maria Augusta and Violete as they break away from the desirable behavior for women in the 20th century. This transgressive behavior is strongly marked by Violete's combative speech when confronting her father: "I shout for the people!" (Amarílis, 1989). Thus, we will seek to demonstrate that pathos is used as a resource that precedes transgressive behavior (hybris). This conduct of female characters represents a reaction to the imposed violence.